Graphic design : the new basics - Lupton, Ellen, 1963-; Phillips, Jennifer C., 1960- (New York : Princeton Architectural Press, 2015)
In graphic design: the new basics, Ellen Lupton and design educator Jennifer Cole Phillips explain the key concepts of visual language that inform any work of design, from a logo or a letterhead to complex websites. Through visual demonstrations and concise commentary, students and professionals explore the formal elements of two-dimensioanl design, such as point, line, plane, scale, hierarchy, layers and transparency. This substantially revised edition presents new chapters on formstorming and Gestalt principles, as well as numerous new examples of student and professional work covering such topics as working whit grids and designing with color.
Includes bibliographical references (pages 260-261) and index.
Keywords: Graphic arts